Creep strains on reinforced concrete columns - Madureira,E. L. (2013)
A concrete element when kept under sustained load presents progressive strain over time, associated to the creep. In reinforced concrete columns, such deformations cause the stress increase in the steel bars of the reinforcement and may induce the material to undergo the yielding phenomenon. The pioneering formulations about the creep effect, developed on the base of creep coefficient, are applicable, especially, when the stress magnitude remains constant. Its application to reinforced concrete members, which exhibits change in stress magnitude, requires simplifications of which result the memory models, which have the disadvantage of requiring the storage of the stress history. To overcome the difficulties related to the excessive demand for computer memory, State models have been developed that dispense such robustness of storage. The subject of this work is the analysis of creep deformations in reinforced concrete columns on the base of a state model fixing its physical parameters from results obtained through the NBR 6118/07 formulation. The results showed that, in the elapse of the phenomenon, occurs stresses transfer from the concrete mass to the reinforcement steel bars which, in turn, have the effect of restrain the creep strains, confirming, in some cases, an imminent material yielding condition.